Pengaruh Bauran Promosi Dan Lokasi Terhadap Keputusan Pembelian di Food Court Margo City Mall Sebagai Penunjang Amenitas Pariwisata di Depok Jawa Barat - Gagih Pradini; Resti Hardini (CV ODIS, 2021)
The purpose of this research is as input to the company in determining the promotion mix strategy and location for improving purchasing decisions. In addition, the research aims to provide a discourse on the tourism sector in restaurant or food court amenities activities in Depok. The results showed that the promotion mix had a positive and significant influence on purchasing decisions. Location also has a positive and significant effect on purchasing decisions. This can provide an illustration that the promotion mix strategy and location of the Margo City Mall food court are well reflected in the behavior of consumers as visitors in using or buying the Food Court at Margo City Mall so that it can support tourism amenities in Depok, West Java.